2021
DOI: 10.15588/1607-3274-2021-1-20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Marine Emergency Response of Electronic Navigation Operator

Abstract: Context. The article introduces an approach for analyzing the reactions of a marine electronic navigation operator as well as automated identification of the likelihood of the negative impact of the human factors in ergatic control systems for sea transport. To meet the target algorithms for providing information referring to the results of human-machine interaction of an operator in marine emergency response situations while managing increasing complexity of navigation operations’ carrying out are put forward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Узагальнено, що особливі освітні потреби в науковому середовищі охоплюють значний пласт змістових ознак з урахуванням зовнішніх чинників, в основному спровокованих нестандартними обставинами. Таке розуміння досліджуваного феномена визначає ставлення представників наукового співтовариства insight.stateuniversity.ks.ua ISSN 2663-970Х (Chen et al, 2023;Kononenko et al, 2020;Rice et al, 2023) and methods of communication and interaction (Kurova et al, 2023), on practices of self-efficacy formation in the leading activity of students and teachers (Celestino et al, 2024;Halian et al, 2023a;2023b), on taking into account the adaptation potential (Blynova et al, 2022;Nosov et al, 2020), on creating conditions for the implementation of acceptable forms of education and the use of health-preserving technologies, the implementation of mixed forms of education, as well as a pedagogical approach to ensure fairness and barrier-free access to information (Masiello et al, 2024) and educational services .…”
Section: On Taking Into Consideration Individual Typological Propertiesunclassified
“…Узагальнено, що особливі освітні потреби в науковому середовищі охоплюють значний пласт змістових ознак з урахуванням зовнішніх чинників, в основному спровокованих нестандартними обставинами. Таке розуміння досліджуваного феномена визначає ставлення представників наукового співтовариства insight.stateuniversity.ks.ua ISSN 2663-970Х (Chen et al, 2023;Kononenko et al, 2020;Rice et al, 2023) and methods of communication and interaction (Kurova et al, 2023), on practices of self-efficacy formation in the leading activity of students and teachers (Celestino et al, 2024;Halian et al, 2023a;2023b), on taking into account the adaptation potential (Blynova et al, 2022;Nosov et al, 2020), on creating conditions for the implementation of acceptable forms of education and the use of health-preserving technologies, the implementation of mixed forms of education, as well as a pedagogical approach to ensure fairness and barrier-free access to information (Masiello et al, 2024) and educational services .…”
Section: On Taking Into Consideration Individual Typological Propertiesunclassified
“…It has been studied that the navigator's motivation is closely related to his expectations, which, in turn, play an important role. On the one hand, this factor can undoubtedly be called formative in creating a behavior strategy, predicting the desired result, but at the same time it is difficult to detect [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The most general feedback loop is concerned with determining whether the result parameters are in accordance with the requirements for achieving the goal. All at the same, intrasystem local feedbacks are tuned to control and correct sequential operation execution (Nosov et al, 2021a). In this regard, N. Bernstein's (2004) studies of movement construction revealed that at any level of movement organization, the implementation of any operation, despite being based on the corresponding subjective motor standard, is always unique.…”
Section: Introductionmentioning
confidence: 99%